Half-life of a secret reckoning with a hidden history - Strasser, Emily (The University Press of Kentucky, 2023)
"In 1942, the US government began construction on a sixty-thousand-acre planned community named Oak Ridge in a rural area west of Knoxville, Tennessee. Unmarked on regional maps, Oak Ridge attracted more than seventy thousand people eager for high-paying wartime jobs. Among them were author Emily Strasser's grandfather George, a chemist. All employees-from scientists to secretaries, from military personnel to construction workers-were restricted by the tightest security. They were provided only the minimum information necessary to perform their jobs. It wasn't until three years later that the citizens of Oak Ridge, and the rest of the world, learned the true purpose of the local industry. Oak Ridge was one of three secret cities constructed by the Manhattan Project for the express purpose of developing the first atomic bomb, which devastated Hiroshima on August 6, 1945. In Half-Life of a Secret: Reckoning with a Hidden History, Emily Strasser exposes the toxic legacy-political, environmental, and personal-that forever polluted her family, a community, the nation, and the world. Sifting through archives and family memories, and traveling to the deserts of Nevada and the living rooms of Hiroshima, she grapples with the far-reaching ramifications of her grandfather's work. She learns that during the three decades he spent building nuclear weapons, George suffered from increasingly debilitating mental illness. Returning to Oak Ridge, Strasser confronts the widespread contamination resulting from nuclear weapons production and the government's disregard for its impact on the environment and public health. With brilliant insight, she reveals the intersections between the culture of secrecy in her family and the institutionalized secrecy within the nuclear industry, which persists, with grave consequences, to this day"--